TINJAUAN YURIDIS TERHADAP HAK DAN KEPENTINGAN PEMEGANG POLIS ASURANSI - Wetmen Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
In everyday human life, there are several problems that pose a risk to oneself, personal belongings or family property, where the risk is something that arises unexpectedly. To overcome these unexpected problems, the role of insurance is very important in providing protection. Insurance is an insurance agreement between the insurance company and the policyholder with the obligation to pay premiums and provide guarantees to pay compensation. In general, the classification of insurance is divided into 3 types, namely: life insurance, general insurance, and reinsurance. The rights of policyholders when viewed from the aspect of consumer protection are regulated in Law Number 8 of 1999 concerning Consumer Protection. Insurance is very closely related to the presence of the OJK Institution as the only institution responsible for insurance companies, as stipulated in OJK Regulation Number 28/POJK.05/2015. The purpose of this journal is to legally review the rights and interests acquired by insurance policy holders. This research uses normative method. The results of the first study, the rights of policyholders have not been explicitly regulated in insurance law. Second, settlement of claim disputes regarding claims for compensation from insurance is regulated in Article 4 paragraph (1) OJK Regulation Number 1/POJK.07/2014, and the third is in insurance laws and regulations in Indonesia, the settlement of insurance cases is handled by OJK and will ends with a court decision.